2006
DOI: 10.1001/archderm.142.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Eosinophilia as an Indicator of Drug-Induced Cutaneous Small-Vessel Vasculitis

Abstract: To determine whether tissue eosinophilia is a reliable indicator of a drug-induced etiology in biopsy samples demonstrating leukocytoclastic vasculitis.Design: Retrospective medical record review with concurrent histopathologic analysis.Setting: University-affiliated dermatology practice.Patients: Sixty-three patients with cutaneous smallvessel vasculitis meeting specific inclusion criteria were divided into drug-induced (n = 16) and non-druginduced (n=47) groups.Main Outcome Measures: Corresponding histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 32 publications
4
42
0
3
Order By: Relevance
“…Microscopic evaluation of the right leg infi ltrate to a mononuclear-predominant infi ltrate (7). Furthermore, drug-induced LCV is often characterized as having an eosinophilic-predominant infi ltrate (8). CZP is approved for treatment of psoriatic arthritis in many countries, including the US (1).…”
Section: Case Presentationmentioning
confidence: 99%
“…Microscopic evaluation of the right leg infi ltrate to a mononuclear-predominant infi ltrate (7). Furthermore, drug-induced LCV is often characterized as having an eosinophilic-predominant infi ltrate (8). CZP is approved for treatment of psoriatic arthritis in many countries, including the US (1).…”
Section: Case Presentationmentioning
confidence: 99%
“…Skin biopsy usually reveals a leukocytoclastic vasculitis (LCV) similar to that seen in other small vessel vasculitis syndromes characterized by vascular and interstitial neutrophilic infiltration, leukocytoclasis, endothelial cell swelling, fibrinoid necrosis, and extravasation of red blood cells (Bahrami et al, 2006). Determining a drug induced versus non-drug induced etiology is a diagnostic dilemma for clinicians and pathologists.…”
Section: Drug Induced Vasculitismentioning
confidence: 99%
“…Determining a drug induced versus non-drug induced etiology is a diagnostic dilemma for clinicians and pathologists. Tissue eosinophilia can be present in drug induced LCV, however, its existence does not exclude other nondrug induced etiologies such as arthropod assault, which will also show prominent interstitial eosinophils (Bahrami et al, 2006). One study suggested the presence of vascular fibrin deposition should exclude a drug related LCV, however, later studies have failed to replicate this findings (Bahrami et al, 2006;Mullick et al, 1979).…”
Section: Drug Induced Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 20% of cases of cutaneous vasculitis represent an adverse drug eruption and most will represent so-called hypersensitivity vasculitis (CLA) and exhibit a superficial dermal, small-vessel neutrophilic vasculitis or lymphocytic vasculitis (Carlson & Chen, 2006;Carlson & Chen, 2007). Identification of tissue eosinophilia in these biopsies is a clue to a drug etiology (Bahrami S, 2006). Pharmacological classes involved in drug-induced vasculitis are: 1. an ANCA-associated group, such as propylthiouracil, hydralazine, allopurinol, minocycline, penicillamine, and phenytoin; 2. an ANCA-negative group, such as colony-stimulating factors, isotretinoin, and methotrexate (Holder SM et al, 2002).…”
Section: Histopathologymentioning
confidence: 99%